2011
DOI: 10.1161/circimaging.110.959742
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion Imaging After Coronary Artery Bypass Surgery Using Cardiovascular Magnetic Resonance

Abstract: Background-Absolute quantification of perfusion with cardiovascular magnetic resonance has not previously been applied in patients with coronary artery bypass grafting (CABG). Owing to increased contrast bolus dispersion due to the greater distance of travel through a bypass graft, this approach may result in systematic underestimation of myocardial blood flow (MBF). As resting MBF remains normal in segments supplied by noncritical coronary stenosis (Ͻ85%), measurement of perfusion in such territories may be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The parameter v e reflects the tissue distribution volume fraction (leakage space) of the contrast agent. An estimate for F (rBF) can be directly measured from the tissue residue function derived from AIF deconvolution (9)(10)(11). Myocardial perfusion MRI studies have indicated reduced flow in MI tissue, assessed through a variety of different perfusion parameters (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…The parameter v e reflects the tissue distribution volume fraction (leakage space) of the contrast agent. An estimate for F (rBF) can be directly measured from the tissue residue function derived from AIF deconvolution (9)(10)(11). Myocardial perfusion MRI studies have indicated reduced flow in MI tissue, assessed through a variety of different perfusion parameters (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…A concern with the use of any first pass perfusion imaging technique in patients with CABG is the increased transit delay in the dynamic contrast delivery to tissue through long graft conduits [ 23 ]. Using model-independent deconvolution analysis, Arnold et al [ 8 ], demonstrated that in the context of rest perfusion, despite a short delay associated with contrast arrival and the resulting increased contrast dispersion particularly involving the internal mammary arterial graft, estimation of MBF was not systematically underestimated in graft subtended myocardial territories. Similarly, using semiquantitative perfusion parameters Kelle et al [ 9 ] showed that grafted and native vessel myocardium shared similar contrast kinetics, despite a short delay in contrast arrival in grafted territories.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, our technical analysis specifically considered the arterial time delay of contrast through the LIMA graft conduit, and did not consider additional dispersion or broadening of the arterial input function. Although the effect of long conduits such as the LIMA graft on contrast dispersion was previously thought to be small [ 8 ], its impact on absolute MBF estimation warrants further evaluation.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Absolute myocardial blood flow (MBF) in mL/min per gram was calculated for each myocardial segment by model-independent deconvolution of myocardial signal intensity curves with the arterial input measured at the basal level. 24,25 Segments with hyperemic MBF below 1.8 mL/min per gram were classified as ischemic. 26 Ischemia burden was defined as the percentage of segments with ischemia.…”
Section: What the Study Addsmentioning
confidence: 99%